Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Join our Q&A platform and connect with professionals ready to provide precise answers to your questions in various areas. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Let's analyze each expression step by step to see if it simplifies to [tex]\(\frac{625}{n^{12}}\)[/tex]:
1. [tex]\(\left(5 n^{-3}\right)^4\)[/tex]
We can apply the power of a power rule to simplify this:
[tex]\[ \left(5 n^{-3}\right)^4 = 5^4 \cdot \left(n^{-3}\right)^4 = 625 \cdot n^{-12} = \frac{625}{n^{12}} \][/tex]
Conclusion: This expression can be simplified as [tex]\(\frac{625}{n^{12}}\)[/tex].
2. [tex]\(\left(5 n^{-3}\right)^{-4}\)[/tex]
We can apply the power of a power rule to simplify this:
[tex]\[ \left(5 n^{-3}\right)^{-4} = 5^{-4} \cdot \left(n^{-3}\right)^{-4} = \frac{1}{5^4} \cdot n^{12} = \frac{1}{625} \cdot n^{12} = \frac{n^{12}}{625} \][/tex]
Conclusion: This expression cannot be simplified as [tex]\(\frac{625}{n^{12}}\)[/tex].
3. [tex]\(\left(5 n^{-4}\right)^3\)[/tex]
We can apply the power of a power rule to simplify this:
[tex]\[ \left(5 n^{-4}\right)^3 = 5^3 \cdot \left(n^{-4}\right)^3 = 125 \cdot n^{-12} = \frac{125}{n^{12}} \][/tex]
Conclusion: This expression cannot be simplified as [tex]\(\frac{625}{n^{12}}\)[/tex].
4. [tex]\(\left(25 n^{-6}\right)^{-2}\)[/tex]
We can apply the power of a power rule to simplify this:
[tex]\[ \left(25 n^{-6}\right)^{-2} = 25^{-2} \cdot \left(n^{-6}\right)^{-2} = \frac{1}{25^2} \cdot n^{12} = \frac{1}{625} \cdot n^{12} = \frac{n^{12}}{625} \][/tex]
Conclusion: This expression cannot be simplified as [tex]\(\frac{625}{n^{12}}\)[/tex].
5. [tex]\(\left(25 n^{-6}\right)^2\)[/tex]
We can apply the power of a power rule to simplify this:
[tex]\[ \left(25 n^{-6}\right)^2 = 25^2 \cdot \left(n^{-6}\right)^2 = 625 \cdot n^{-12} = \frac{625}{n^{12}} \][/tex]
Conclusion: This expression can be simplified as [tex]\(\frac{625}{n^{12}}\)[/tex].
### Summary
The expressions that can be simplified to [tex]\(\frac{625}{n^{12}}\)[/tex] are:
- [tex]\(\left(5 n^{-3}\right)^4\)[/tex]
- [tex]\(\left(25 n^{-6}\right)^2\)[/tex]
Thus, the indices of the expressions which can be simplified to [tex]\(\frac{625}{n^{12}}\)[/tex] are expressions 1 and 5.
1. [tex]\(\left(5 n^{-3}\right)^4\)[/tex]
We can apply the power of a power rule to simplify this:
[tex]\[ \left(5 n^{-3}\right)^4 = 5^4 \cdot \left(n^{-3}\right)^4 = 625 \cdot n^{-12} = \frac{625}{n^{12}} \][/tex]
Conclusion: This expression can be simplified as [tex]\(\frac{625}{n^{12}}\)[/tex].
2. [tex]\(\left(5 n^{-3}\right)^{-4}\)[/tex]
We can apply the power of a power rule to simplify this:
[tex]\[ \left(5 n^{-3}\right)^{-4} = 5^{-4} \cdot \left(n^{-3}\right)^{-4} = \frac{1}{5^4} \cdot n^{12} = \frac{1}{625} \cdot n^{12} = \frac{n^{12}}{625} \][/tex]
Conclusion: This expression cannot be simplified as [tex]\(\frac{625}{n^{12}}\)[/tex].
3. [tex]\(\left(5 n^{-4}\right)^3\)[/tex]
We can apply the power of a power rule to simplify this:
[tex]\[ \left(5 n^{-4}\right)^3 = 5^3 \cdot \left(n^{-4}\right)^3 = 125 \cdot n^{-12} = \frac{125}{n^{12}} \][/tex]
Conclusion: This expression cannot be simplified as [tex]\(\frac{625}{n^{12}}\)[/tex].
4. [tex]\(\left(25 n^{-6}\right)^{-2}\)[/tex]
We can apply the power of a power rule to simplify this:
[tex]\[ \left(25 n^{-6}\right)^{-2} = 25^{-2} \cdot \left(n^{-6}\right)^{-2} = \frac{1}{25^2} \cdot n^{12} = \frac{1}{625} \cdot n^{12} = \frac{n^{12}}{625} \][/tex]
Conclusion: This expression cannot be simplified as [tex]\(\frac{625}{n^{12}}\)[/tex].
5. [tex]\(\left(25 n^{-6}\right)^2\)[/tex]
We can apply the power of a power rule to simplify this:
[tex]\[ \left(25 n^{-6}\right)^2 = 25^2 \cdot \left(n^{-6}\right)^2 = 625 \cdot n^{-12} = \frac{625}{n^{12}} \][/tex]
Conclusion: This expression can be simplified as [tex]\(\frac{625}{n^{12}}\)[/tex].
### Summary
The expressions that can be simplified to [tex]\(\frac{625}{n^{12}}\)[/tex] are:
- [tex]\(\left(5 n^{-3}\right)^4\)[/tex]
- [tex]\(\left(25 n^{-6}\right)^2\)[/tex]
Thus, the indices of the expressions which can be simplified to [tex]\(\frac{625}{n^{12}}\)[/tex] are expressions 1 and 5.
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.